PENGAWASAN PROGRAM SIARAN TELEVISI BERASARKAN STANDAR PROGRAM SIARAN OLEH KOMISI PENYIARAN INDONESIA DAERAH (KPID) RIAU - Ratih Sabriah Harahap; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Today the development of television throughout Indonesia very rapidly, causing the creativity and competition among broadcasters higher. So the quality of the broadcast program a barometer of success make a profit. Due to the increasing levels of competition between broadcasters, then the potential for broadcasters to bring up the broadcast program that is incompatible with thee values professed and believed by the public. It can be seen from the spectacle that does not educate and impact of the broadcast to the public, especially in the province of Riau. This study was conducted to determine Television Broadcast Program based on Standard Broadcasting Program conducted by KPID Riau. The research was conducted using qualitative methods, with descriptive research. This research use Handoko Theory with Determination Standards, Determination of Implementation Activities Measurement, Benchmarking Implementation of Standards and analysis of irregularities, taking corrective action. The method used in this research is the method of observation, interviews and documentation by using descriptive and qualitative analysis techniques. Things that have been found in this research is first, the supervision by the Indonesian Broadcasting Commission of Riau is quite optimal. Second, the television broadcasters are still many who are not guided by the Standard of the broadcast program. Third, there is still a lack of socialization to standards and media literacy programs broadcast by KPID Riu. Fourth, there is still a lack of public understanding of the broadcast was good to watch and not good.Keywords : Control, Television Broadcast Program, Standard Broadcasting Program